Kant on Emotions Critical Essays in the Contemporary Context - Angelucci, Daniela; Borges, Maria; Cvejić, Igor; Failla, Mariannina; Falcato, Ana Cristina; Feloj, Serena; González, Ana Marta; Mendonça, Dina; Sánchez Madrid, Nuria; Teruel, Pedro Jesús; Velasco, Josefa Ros (New studies in the history and historiography of philosophy ;, 2021)
Kant's account of emotions has only recently begun to receive the attention that this topic deserves, as it casts new light over the manifold features of transcendental philosophy. The authors expand the contemporary overview of the Kantian treatment from both a neuroscientific and a continental philosophical perspective. The volume opens paths to reevaluate neglected aspects of the Kantian model of human rationality.